2024
DOI: 10.1590/1519-6984.273386
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in a core collection of Iranian sour cherry

Abstract: The exploitation of plant genetic resources is an important and rapid strategy to release commercial cultivars. In this study, 234 sour cherry genotypes were collected from various locations of Iran and phenotypically assessed according to IPGRI and UPOV descriptors. The genotypes were grafted onto Mahaleb rootstock and were planted in Horticultural Science Research Institute (HSRI) core collection in Karaj, Iran. In this study, 22 different characteristics were measured in the sour cherry genotypes. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…This study also found that the correlations for persimmon fruit growth were not only between the different parts of the fruit but also between the fruit and its supporting tissues. Our results show that fruit handle width was highly significantly and positively correlated with fruit size traits, such as fruit transverse and longitudinal length, which is consistent with previous studies on the morphological diversity in Diospyros kaki [24], Cerasus pseudocerasus [53], and Citrus clementina [54]. These relationships may be partly explained by the fruit handle width being an external connective tissue of the fruit and its nutrient transport and weight support functions for fruit development.…”
Section: Discussionsupporting
confidence: 91%
“…This study also found that the correlations for persimmon fruit growth were not only between the different parts of the fruit but also between the fruit and its supporting tissues. Our results show that fruit handle width was highly significantly and positively correlated with fruit size traits, such as fruit transverse and longitudinal length, which is consistent with previous studies on the morphological diversity in Diospyros kaki [24], Cerasus pseudocerasus [53], and Citrus clementina [54]. These relationships may be partly explained by the fruit handle width being an external connective tissue of the fruit and its nutrient transport and weight support functions for fruit development.…”
Section: Discussionsupporting
confidence: 91%
“…It is a difficult challenge to analyze sour cherries because they are tetraploid and most of the statistical analysis techniques and software used molecular genetics are designed for diploid species or dominant features. Moreover, diversity analyses in sour cherries are usually based on morphological characteristics [57]; only a few studies have applied genetic markers to examine them [7,58]. In the present study, twelve molecular markers were used to analyze and characterize the genetic diversity of sour cherries cultivated in Similarly, for ripening time, the group numbers are as follows: 1 corresponds to fruits ripening before June 5th, 2 corresponds to fruits ripening between June 5th and 15th, 3 corresponds to fruits ripening between June 15th and 25th, and 4 corresponds to fruits ripening after June 25th.…”
Section: Discussionmentioning
confidence: 99%